Evaluation of long-term hard tissue relapse following surgical–orthodontic treatment in skeletal class II patients: A systematic review and meta-analysis. Issue 4 (April 2021) - Gaitan-Romero, L.; Shujaat, S.; Ma, H.; Orhan, K.; Shaheen, E.; Mulier, D.; Willems, G.; Politis, C.; Jacobs, R.
Abstract: This systematic review and meta-analysis was performed to evaluate the long-term hard tissue stability and relapse factors following surgical–orthodontic treatment in skeletal class II patients. A literature search was conducted using Embase, Cochrane Central, Web of Science, and PubMed, yielding 3184 articles published up to January 2019. Risk of bias was assessed following the Cochrane handbook. Ten articles met the inclusion criteria. A total of 1079 patients were followed up for 5–13 years. The qualitative findings showed a variety of extrinsic and intrinsic factors affecting long-term stability. Meta-analysis for the amount and direction of cephalometric landmark displacement in the vertical and sagittal planes showed significant angular increases of ANB and backward relapse of SNB, however within the clinically acceptable range of 4°. In relation to linear measurements, the mean differences in all landmarks were within the clinically acceptable range of 2 mm except for gonion. In conclusion, this systematic review showed multiple intrinsic and extrinsic factors responsible for relapse. However, the outcomes of the meta-analysis are limited due to the heterogeneity of data, small number of studies, and inconsistent methods of evaluation. Further high-quality studies utilising standardised three-dimensional methodologies are required to improve the level of evidence.